The Uncertain Art of Management - Onsman, Habby; Series Editor Carolyn Barker; Associate Editor Robyn Coy (Sydney McGraw Hill, 2003)
Explores a wide range of practical and theoretical concerns that have confused, concerned and exasperated managers at all levels in modern Australian organisations. This book will be of interest to every practising manager grappling with the complexities of today's corporate life
Include Index
Keywords: Management -- Australia -- Leadership